Rwanda : Staff Report for the 2014 Article IV Consultation and Second Review Under the Policy Support Instrument. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2014 Article IV Consultation and Second Review Under the Policy Support Instrument highlights that Rwanda's economic performance since the turn of the century has been remarkable. Strong policies have played a key role in maintaining real GDP growth at 7.8 percent on average since 2000, with significant poverty reduction. The economy is recovering from the disruptions induced by aid suspension through mid-2013, with growth bouncing back in the first half of 2014 and inflation well contained. Growth in 2014 is expected to be about 6 percent, rising to the longer-term growth rate of 7.5 percent in the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet